Stockwell transform for estimating decay time at low frequencies. (17th February 2021) - Čurović, Luka; Murovec, Jure; Novaković, Tadej; Prislan, Rok; Prezelj, Jurij
Abstract: Reverberation is one of the most fundamental phenomena that describes the acoustics of an enclosure. Due to the modal behaviour of the room, the measured Schroeder decay functions may exhibit double or multiple slopes at wavelengths comparable to the dimensions of the room. In such a case the evaluation of reverberation parameters (e.g. T 20, T 30 ) according to standardized measurement procedures [1, 2, 3] becomes erroneous. To overcome these shortcomings the applied filters and the analysis must take into account the modal nature of the measured response. In this work, the use of the window optimized time-frequency Stockwell transform ( S -transform) to determine the decay time and the modal frequencies from a room impulse response is investigated. The estimation of the decay time is discussed in terms of synthesized and measured decays. The applicability of the proposed method is investigated through simple examples using the Prony model. The method is also tested against noise in the signal. The measurements are carried out in a test chamber with and without an absorptive element to investigate the influence of absorption on the decay process. The simulation and experimental results show that the proposed method can be used to estimate the decay times of modes which would produce multiple sloped decays if observed in standardized frequency bands.